1984
DOI: 10.1038/sc.1984.37
|View full text |Cite
|
Sign up to set email alerts
|

Nicergoline in the treatment of neuropathic bladder dysfunction: a preliminary report

Abstract: Summary. We have employed the alpha blocking drug Nicergoline in 14 patients with neuropathic bladder dysfunction of the upper motor neurone type.The oral administration of 15-30 mgrs/ day of this drug over a period of 9·5 months significantly improved the urodynamic parameters, with an increase of bladder capacity, a disappearance or amelioration of uninhibited bladder contrac tions and a decrease in urethral pressure, profile urethral length and residual urine.Two patients with vesico-ureteral reflux present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Various studies have reported other minor effects with nicergoline; these include hot flushes [37, 42], dizziness [41], inhibition of ejaculation [43], and interstitial nephritis [44]. While hot flushes can be due to the effects of nicergoline on blood vessels, inhibition of ejaculation is a known side-effect of alpha adrenergic blockers.…”
Section: Concerns Regarding Safety Of Nicergolinementioning
confidence: 99%
“…Various studies have reported other minor effects with nicergoline; these include hot flushes [37, 42], dizziness [41], inhibition of ejaculation [43], and interstitial nephritis [44]. While hot flushes can be due to the effects of nicergoline on blood vessels, inhibition of ejaculation is a known side-effect of alpha adrenergic blockers.…”
Section: Concerns Regarding Safety Of Nicergolinementioning
confidence: 99%
“…Various studies have reported other minor effects with nicergoline including hot flushes, dizziness, ejaculation failure and interstitial nephritis 42 43…”
Section: Discussionmentioning
confidence: 99%